FORUM MŁODYCH CHIRURGÓWAbnormal origin of the right internal thoracic artery – case report - Olszówka, Piotr; Kolowca, Maciej; Stącel, Tomasz; Widenka, Kazimierz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Currently right mammary artery is more frequently used in cardiac surgery. We are presenting an anomaly of the right intra thoracic artery revealed during coronary artery bypass grafting. Described artery was arising from intercostal artery. Because of that in presented case it was not used for grafting. These findings may be important for the cardiologists in preoperative coronary angiography as also in postoperative period.